Almost none of the sequences of 0's and 1's are almost convergent - Jeff Connor (International Journal of Mathematics and Mathematical Sciences)
We establish that, in the sense of the Law of Large Numbers, almost none of the sequences of 0’s and 1’s are assigned the same value by every Banach limit.